2020
DOI: 10.1016/j.brs.2019.11.013
|View full text |Cite
|
Sign up to set email alerts
|

High density microelectrode recording predicts span of therapeutic tissue activation volumes in subthalamic deep brain stimulation for Parkinson disease

Abstract: Background: Subthalamic deep brain stimulation alleviates motor symptoms of Parkinson disease by activating precise volumes of neural tissue. While electrophysiological and anatomical correlates of clinically effective electrode sites have been described, therapeutic stimulation likely acts through multiple distinct neural populations, necessitating characterization of the full span of tissue activation. Microelectrode recordings have yet to be mapped to therapeutic tissue activation volumes and surveyed for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…Interestingly, we also noted HFOs above STN in three patients (see Figure 2E). This activity could be originating from other structures such as thalamus or zona incerta (ZI) (Thompson et al, 2014;Yang et al, 2014;Lu et al, 2019;Meidahl et al, 2019). Previous work has shown that dorsolateral STN and ZI stimulation provides the greatest improvement in PD motor symptoms (Gourisankar et al, 2018), which correlates with our observation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, we also noted HFOs above STN in three patients (see Figure 2E). This activity could be originating from other structures such as thalamus or zona incerta (ZI) (Thompson et al, 2014;Yang et al, 2014;Lu et al, 2019;Meidahl et al, 2019). Previous work has shown that dorsolateral STN and ZI stimulation provides the greatest improvement in PD motor symptoms (Gourisankar et al, 2018), which correlates with our observation.…”
Section: Discussionsupporting
confidence: 89%
“…However, the volatile interface stability and increased computational power requirement arising from higher sampling rates might still favor LFPs (Rouse et al, 2011;Buzsáki et al, 2012;Priori et al, 2013;Thompson et al, 2014). Growing literature supports the utility of LFPs in intraoperative mapping (Chen et al, 2006;Przybyszewski et al, 2016;Telkes et al, 2016;Kolb et al, 2017;Lu et al, 2019). Our results also support the use of LFPs intraoperatively for DBS lead implantation.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…High accuracy region SVM classification models were used by Guillén et al [92,93] with a 99.5% accuracy at stratifying MERs between the STN, thalamus nucleus, and the substantia nigra. Similarly, Lu et al [94] applied SVM to 16 subjects' MERs guided by 3-Tesla MRIs. This model achieved an AUC of 0.87.…”
Section: Surgical Targetingmentioning
confidence: 99%
“…Several previous studies have shown the association of dorsolateral posterior STN field potentials and firing rate to effective clinical outcome 13 15 , quantification of motor subtypes 16 , severity of rigidity and bradykinesia in PD 17 , optimal DBS implantation trajectory 18 and simulation parameters 19 among others. Recent studies have further used various recordings using MER for localizing dorsal–ventral border of STN 20 and predicting therapeutic volume of tissue activation 21 . Despite extensive research in the pathophysiological role and clinical correlation of these electrophysiological activity patterns in PD and target localization, studies focusing on the differential use of them for improving the accurate implantation of the electrodes in sensorimotor region of STN is still insufficient.…”
Section: Introductionmentioning
confidence: 99%